To find the product of the two expressions \((x^2y + 2)(x^2 - y)\), we can use the distributive property (also known as the FOIL method for binomials):
\[ (x^2y + 2)(x^2 - y) \]
We'll distribute each term in the first expression to each term in the second expression:
- \(x^2y \cdot x^2 = x^4y\)
- \(x^2y \cdot (-y) = -x^2y^2\)
- \(2 \cdot x^2 = 2x^2\)
- \(2 \cdot (-y) = -2y\)
Now, we combine all these results:
\[ x^4y - x^2y^2 + 2x^2 - 2y \]
Thus, the product \((x^2y + 2)(x^2 - y)\) is:
\[ \boxed{x^4y - x^2y^2 + 2x^2 - 2y} \]